External communication strategy in hospital services - Yagén María Pomares Pérez; Yuliett Mora Pérez; Pavel Noa Rodríguez; Jorge Luis Nodal Cordero; Mariela García Velázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
In hospital services context, it is important to consider what refers to external communication, given the need to properly guide the link with the rest of society; in this sense, it is necessary to organize and promote relationships with other institutions. The ways to achieve this purpose have been the object of attention and study for several decades. This article aims to systematize knowledge about external communication strategies in hospital services. A narrative review was carried out in data banks: VHL, PubMed, and SciELO, according to the indexed descriptors. Seven articles developed in different countries were included in the analysis. Among the specific components of this type of strategy, there are organizational information diagnoses; policies; strategies; communicative products, informational products and services; information and communication structures and their managers; skills training programs; as well as control, monitoring and evaluation of the results of each activity, together with the action of a multidisciplinary team that enhances all this development.